The role of the PKCζ/JNK signaling pathway in regulating the development of femoral head necrosis - Miaofeng Hu; Cheng Li; Qi Sun; Baisong Hu; Jiong Yang; Xiufeng Wang; Jinshan Huang; Di Shen (Brazilian Journal of Medical and Biological Research, 2025)
Osteonecrosis of the femoral head (ONFH) is a debilitating condition characterized by the death of bone cells in the hip joint, resulting in profound disability. This condition has a significant global prevalence. Glucocorticoid (GC)-induced apoptosis of bone cells serves as a crucial cellular mechanism underlying ONFH. The protein kinase C zeta (PKCζ) and c-Jun N-terminal kinase (JNK)/c-Jun cascades have been implicated in the progression of ONFH, yet their interrelationship and contributions to disease development remain unclear. The objective of this study was to investigate the combined impact of PKCζ and JNK/c-Jun signaling on dexamethasone (Dex)-induced apoptosis in osteoblasts in vitro and in GC-induced ONFH rat models in vivo. In vitro experiments were conducted using hFOB1.19 osteoblastic cells to scrutinize the effects of Dex-induced apoptosis. The role of the PKCζ/JNK/c-Jun signaling pathway in this process was examined using naringenin-7-O-β-D-Glucuronide (N7G), a PKC inhibitor, and anisomycin, a JNK activator. The findings were further validated using a rat model of ONFH in vivo. Our results revealed that PKCζ activation augmented JNK/c-Jun signaling and facilitated Dex-induced osteoblast apoptosis. Inhibition of PKCζ with N7G mitigated these effects, while JNK activation with anisomycin intensified them. Similar regulatory effects on osteoblast apoptosis and ONFH progression were observed in the in vivo rat models. Glucocorticoids can induce osteoblast apoptosis and contribute to the development of ONFH by activating the PKCζ/JNK/c-Jun signaling pathway. This study provides compelling evidence supporting the potential therapeutic value of comprehending the pathogenesis of ONFH and developing targeted treatments for this debilitating condition.